Did de‐policing cause the increase in homicide rates? - Rosenfeld, Richard (Criminology & public policy, 2019)
Widespread protests and demands for accountability in the wake of broadly publicized police killings of unarmed civilians coincided with the marked upturn in homicide levels, especially in large U.S. cities, in 2015. Many observers, including prominent political figures, claimed that de‐policing caused the homicide rate to rise: Fearing increased legal liability and publicity, the police employed less proactive enforcement and made fewer arrests, producing an increase in homicide levels. We use structural equation modeling to estimate the simultaneous relationship between arrest and homicide rates between 2010 and 2015 in 53 large cities. We find no evidence of an effect of arrest rates on city homicide rates for any offense category for any year in this period, including 2015, the year of the spike in homicide levels.